Sea ice concentration inversion based on different Arctic sea ice types - Wang, Xingdong; Sun, Zehao; Guo, Zhi; Zhao, Yanchuang; Wang, Yuhua (Frontiers in Marine Science, 2024)
In response to the problem that the ASI algorithm cannot fully consider the differences between different sea regions and the impact of different sea ice characteristics on the inversion results of sea ice concentration (SIC) in the entire polar regions due to the use of the same sea ice and seawater tie-points. The SIC inversion algorithm based on different types of Arctic sea ice is proposed. The proposed algorithm selects pure ice and pure water sample points in different sea regions to derive SIC inversion formulas, and subsequently obtains SIC retrieval results for the entire Arctic.Compare the results of this study with those of traditional ASI algorithm, and perform local validation based on the sea ice distribution obtained from Landsat-8 data. The results show that the sea ice distribution obtained by the proposed algorithm is closer to the results obtained from Landsat-8 data, and the accuracy of SIC inversion is higher than that of the ASI algorithm.1.